2020
DOI: 10.2196/17577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Patient-Centered Mobile Health Technologies: Definitions, Methodologies, and Outcomes

Abstract: Several recently published studies and consensus statements have demonstrated that there is only modest (and in many cases, low-quality) evidence that mobile health (mHealth) can improve patient clinical outcomes such as the length of stay or reduction of readmissions. There is also uncertainty as to whether mHealth can improve patient-centered outcomes such as patient engagement or patient satisfaction. One principal challenge behind the “effectiveness” research in this field is a lack of common understanding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Patients are more likely to engage with digital tools when no action is required, but they merely provide information and data about health issues (Bruce et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients are more likely to engage with digital tools when no action is required, but they merely provide information and data about health issues (Bruce et al. , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Engaging patients in service co-production (Green cluster). Patients are more likely to engage with digital tools when no action is required, but they merely provide information and data about health issues (Bruce et al, 2020). Such information permits patients to obtain insights about their health condition, nurturing a greater awareness of health determinants, without necessarily implying the adoption of self-care behaviors (Hudson et al, 2020).…”
Section: Thematic Clustersmentioning
confidence: 99%
“…Risk of bias; inconsistency; differences in patient populations, settings, and interventions; imprecision; publication bias; and the underreporting of relevant information have been listed as the main reasons why previous reports have only provided low-quality evidence concerning the effectiveness of digital counseling approaches. In addition, the heterogeneity in eHealth definitions also makes between-study comparisons difficult, which are necessary to provide health care professionals with evidence-based recommendations [ 30 , 48 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed promising results on enhancing selfawareness towards a healthy lifestyle and behavioral change, effective engagement, and self-reporting to manage the factors that impact obesity or overweight. McCurdie et al [30] and Bruce et al [31] adopted a UCD evidence-based approach to develop a mHealth consumer app to enhance healthcare delivery and clinical outcomes with remote patient monitoring and early detection of health risks to avoid severe damages. Their research reveals the importance of a user-centered/patient-centered approach in achieving user engagement (or user evaluation) to enhance the effectiveness of behavioral interventions.…”
Section: Non-iterative Approachmentioning
confidence: 99%